STUDY OF PROFESSIONAL DEVELOPMENT AND CAREER ENGLISH TEACHER - Meilan Nirmala Shinta (LP2M IAIN Sultan Amai Gorontalo, 2018)
This study aims: 1). describe the process of teachers in fulfilling their professional qualifications and career development process 2). searching information inhibiting things by the teacher in fulfilling professional and career development. The scope of the research focuses 2 of 4 competencies that must be possessed by a teacher namely: pedagogic competence and professional competence. The method of this research is descriptive qualitative with case study approach. The subject of this study using the principle of purposive sampling that there are 3 English teachers who became the subject in this study. Interview (deep interview) and observation (passive observer). The results of this study illustrate that: 1). Pedagogic competence: for teachers who have attended a learning-based IT training tend to apply a scientific approach in learning English in class K13 than teachers who have never followed it, teachers use IT media in teaching in the form of LCD and material from the internet, and be creative according to facilities and infrastructure which exists; professional competence: MGMP activities for urban municipal teachers in Kendari show that the activity is active, whereas for teachers teaching in villages in other districts the activities are not routine, PTK research is based on the needs of the rank and prerequisite of certain activities not based on teacher needs, training activities and workshops show as activities that are generally followed by teachers. 2). Things that become obstacles include: Pedagogic competence: systemic that is a periodic in-depth workshop curriculum so that the understanding of teachers that still need to be upgraded must be dealing with the implementation of the curriculum that must be run, facilities that are not yet sufficient to assist in learning in class, which is still low especially in the regions; obstacles to the professional competence of MGMP activities that are not routine in the regions, MGMP instructors who trained are not appropriate in their fields, the burden of teacher responsibility and so many become one of the PTK factors is not a priority of teachers implement it, there is no system that is presenting the results of teacher PTK not only as admisnistrasi requirements alone. The conclusion is still need to improve the system of teacher competency activities in the pedagogic and professional sections so that the process of professionalism improvement and career of teacher can be more meaningful and useful in developing teacher task.